Gayo's Scientific Network, Samalanga, Thawalib to Candung Era 1900-1986 - Ihsan Harun; Emy Yusdiana; Saifullah Saifullah (Budapest International Research and Critics University, 2020)
The history of the network growth between knowledge claimants from Gayo and scholars in the Aceh Coast, West Sumatra and Bangil, East Java, involves a very complex historical process-The network of students and teachers was created to change the mindset of knowledge claimants which later gave birth to a renewal of Islamic education in Gayo during the Era 1900-1986 years. There are two network models that occur, namely the network of figures and institutions. In order to accurately understand the form of interaction and relationship between these three areas and the historical dynamics depicted in Gayo Islamic education, it is described and presented in this paper.